If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(-1 + 2n) = 45 (-1 * -5 + 2n * -5) = 45 (5 + -10n) = 45 Solving 5 + -10n = 45 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -10n = 45 + -5 Combine like terms: 5 + -5 = 0 0 + -10n = 45 + -5 -10n = 45 + -5 Combine like terms: 45 + -5 = 40 -10n = 40 Divide each side by '-10'. n = -4 Simplifying n = -4
| -2-2(1-6r)=7(r-4)-1 | | 8/B=4/13 | | 3(x-4)+2x=4x+5 | | 64=-4a-5(2a+4) | | 0.33333333(15w+975)=3160 | | X-6x+3x-7x= | | -5y-3(-2z+4y)+3z= | | 5(2x-3)+3=68 | | 0.33333333(15w+975)=4000 | | X(2)+8x-20=0 | | 5(m+10)=25 | | x^2+6x-4y+29=0 | | 10+9x=26+1x | | -4+4(5x+2)=-36 | | 2/5x-4/3x^2 | | 1.2(5x-12)=2x-3+10y | | 5y=4sinx-3 | | 4(n+1)=24 | | -42=-6(1-3x) | | (x+18)*2=4x-12 | | 1+3x+94=180 | | 1/8-y/9=1/72 | | -2m+5=14+m | | 36-7c=22 | | -5r-8=-5r-16 | | 5x^2=170 | | 5x+6y=9y+1 | | 1-5/6-1/12 | | 9z-2m+2-3= | | 10=n-8+2n | | 1+5n=10 | | 46+3x+2x-1=180 |